(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In-vitro cytotoxicity assays are laboratory techniques used to evaluate the toxicity of substances, such as drugs or chemicals, on cultured cells. These assays help determine the potential harmful effects of these substances on cell viability, proliferation, and function before they are tested in vivo (in living organisms). Adina cordifolia is a plant known for its medicinal properties, particularly in traditional medicine. Its phytoconstituents have been the subject of various studies due to their potential therapeutic effects.